MOTIVASI BURUH PEREMPUAN BEKERJA DI PT KHARISMA RIAU SENTOSA PRIMA DI DESA TALANG SUKA MAJU KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Susi Susanti; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of Talang Suka Maju in Rakit Kulim districts.This village was chosen, due to this village there is a new plantation which create new jobopportunities for men and women. The aim of this study was to determine what caused themotivation of women workers interested in working in PT Kharisma Riau Sentosa Prima and todetermine what factors influence the motivation of the women workers working in PT KharismaRiau Sentosa Prima.The population in this study were all female workers who work in PT Kharisma RiauSentosa Prima. Sampling in this study is the engineering method of census sampling techniquewhen all members of the population sampled.The research method of this research is to use descriptive quantitative method. Theprocess of collecting data using the method of observation and questionnaires.Keywords: Motivation workers, Women Work.